Adaptive Vocational Curriculum Transformation through the Digitalization of Local Product Marketing for the Empowerment of Human Resources with Intellectual Disabilities - Al Shaffaat Ronvy; Yolanda Desti; Hafiz Hidayat (Indonesian Counselor Association (IKI), 2025)
The rapid development of digital technology demands vocational education that is more inclusive and aligned with contemporary economic needs. However, vocational learning for students with intellectual disabilities in special schools generally remains focused on product creation without integrating digital marketing skills. This study aims to develop an adaptive vocational curriculum based on digital marketing for students with intellectual disabilities at SLB C Payakumbuh. The research employed a Research and Development approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages to produce an adaptive digital marketing–based vocational curriculum module. Data were collected through needs assessment, expert validation, observation, and interviews, and analyzed descriptively. The results indicate that the developed curriculum module is feasible for use, improves teachers’ understanding of digital marketing–based vocational learning, and supports students’ initial abilities to market vocational products with varying levels of independence. This study highlights the importance of integrating digital marketing into vocational curricula to support the empowerment and early economic independence of students with intellectual disabilities.